PENGARUH PENGGUNAAN MODEL PEMBELAJARAN DEMONSTRASI TERHADAP HASIL BELAJAR TEKNIK PERAKITAN ELEKTRONIKA (TPE) KELAS X TEKNIK AUDIO VIDEO DI SMK NEGERI 5 PADANG - Peri Ardiansah; Hanesman Hanesman; Nelda Azhar (Universitas Negeri Padang, 2016)
The problem in this study is the low learning outcomes achieved by students on the subjects of Electronics Assembly Techniques which is below the minimum completeness criteria (KKM) set a school that is 75. This is presumably because they are learning is often used during the learning direct model is applied directly proven yet effective.The purpose of this research is to reveal how much influence the Demonstrasion learning model to study the results of class X TAV students on subjects Electronics Assembly Techniques (TPE).This research is an experimental study. The sample were students of class X TAV at SMKN5 Padang Academic Year 2014 / 2015.Class experiment is treated using Demonstrasion Learning Model and the control group is a class that uses the direct teaching model.The data is taken from the test results in the form of student practicum. Data were analyzed manually to test for normality, homogenity testing, and hypothesis testing. The research test result obtained value of average student which using model demonstrasion is 80,06 while student who use learning direct model lower is 71,60 with the percentage effect is 11,81%. The result of the calculation hypothesis at significance level α = 0.05 was found that t count> t table is 2,36>2,048. The results of these tests give an interpretation that H0 is rejected and H1 is accepted, this means that on average significantly experimental class learning outcomes greater than the average control class learning outcomes. Key Words: Demonstrasion Learning Model, Learning Direct, Control and Exsperiment